Well lets see:
2y = 6x+8
y=3x+4 does not equal y=3x+6
So they are not the same.
3x + 2y = 7
2y = 6x+2
(2, -1)
If: 3x+2y = 5x+2y = 7 which is the same as 7 = 7 = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtracting equations: x = 0 Therefore by substitution: x = 0 and y = 3.5
3x-2y-7=0
-3x + 2y = 9 2y = 3x + 9y = 1,5x + 4,5
3x + 2y = 7
2y = 6x+2
(2, -1)
If: 3x+2y = 5x+2y = 7 which is the same as 7 = 7 = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtracting equations: x = 0 Therefore by substitution: x = 0 and y = 3.5
3x-2y-7=0
3x+2y=9 2y=9-3x y=-1.5x-4.5
3x+2y = 1 2y = -3x+1 y = -1.5x+0.5
3x+2y=6 2y=-3x+6 y=-1.5x+3
3x = 2y + 7 The standard form is: 3x - 2y - 7 = 0
3x+2y-5=0 3x+2y=5 Im lost im only 12 work out the rest hope i helped
3x + 2y = 8 This is an equation. It could be the equation of a line.